Active Labor Market Programs for Youth : A Framework to Guide Youth Employment Interventions - Cunningham, Wendy; Sanchez-Puerta, Maria Laura; Wuermli, Alice (World Bank, Washington, DC, 2012)
Youth are three times more likely to be unemployed than adults, even in economies with strong economic growth. This note is a tool to provide policymakers and youth-serving organizations with a framework to better diagnose short- to medium-run constraints facing the stock of unemployed youth and to design evidence based youth employment interventions. The note only addresses youth employment; strategies to affect wages, productivity, underemployment, or job quality are not directly discussed. This note presents youth-oriented Active Labor Market Programs (ALMPs) that conform to one of two criteria. Each intervention either has been shown to have predominately positive impact, as measured by rigorous impact evaluations, or has weaker evidence of impact-rigorous evaluations with mixed evidence of impact or strong positive monitoring data-and is theoretically sound. Cost-effectiveness information is presented when available. The note focuses on programs that are appropriate to address constraints faced by youth from disadvantaged backgrounds.